Country Files
The series contains press releases and clippings, media monitoring materials, memos (fax and e-mail), correspondence, human rights listserv materials, and reports and publications from other human rights organizations. The Country Files series consists of a vast array of documents from a variety of sources on the political, economic and social background of virtually all 47 members of the Council of Europe, as well as Belarus and the Central Asian countries, but also individual territories whose legal status is contested or not widely recognized, such as Kosovo or Chechnya. Some countries or geographic regions, including the USSR/Russia, Central Asia, Turkey, the Caucasus, or Bosnia and Herzegovina, which were more visible on the IHF’s monitoring radar at certain points in time, are better represented in the files. Beyond the general portray of a particular country in a given period of time, specific issues are also revealed in the documents: from freedom of religion in France through torture and prison conditions in Turkey to hate speech and war crimes in South Eastern Europe. Obviously, the focus is mainly directed on human rights violations of various degrees, such as genocide, war crimes, ethnic cleansing and persecution of national minorities, destruction of cultural property, inhuman prison conditions, censorship and breaches of freedom of religion and free expression. A significant quantity of the documents deal with the persecution of human rights activists and the indictment and censure of other human rights advocates, including journalists, writers and scientists. The collection is especially valuable for researchers interested in grave human rights abuses such as censorship, detention, torture, or forced medical treatment in Communist dictatorships; in the collapse of the Soviet Union or Yugoslavia, and the emergence of transitional democracies in their places; and also for those concerned with the mushrooming of alarming tendencies along with them: internal displacement and forced migration, ethnic conflicts, xenophobia and election violence. Containing materials from many different Western and regional sources, the voluminous Kosovo files give a full insight into the humanitarian catastrophe in the Albanian enclave of the former Yugoslavia, from random clashes and violence through the exodus of Kosovar Albanians to the air raids by NATO forces. Accruals not expected